Fille d’Octobre. Générations, engagement et histoire - Malika Rahal (L’Année du Maghreb)
This article first appeared as an online research blog, Textures of Time. It assumes the form of an ego-history. Herself one of the «children of October» (October 1988 and the heavily repressed Algerian youth riots), the author reflects upon the possibility of being both Algerian and French on one side and the other of the Mediterranean in the context of emigration, and on the necessity for all historians working on Algeria to be self-critical about their generational, national (or transnational) and social engagements.* Ego-histories are commissioned biographical essays in which the author is invited to explore his or her vocational choices. The essay form was invented by French Academician, Historian and Editor, Pierre Nora for a collection published in 1987 as Ego-histories.